Financial Statement Analysis of Fraud With Hexagon Theory Fraud Approach - Akbar, Raihan Noval; Zakaria, Adam; Prihatni, Rida (LPPM Universitas Negeri Jakarta, 2022)
This research was conducted to find the effect of shareshexagon theory that consisted of stimulus, capability, collusion, opportunity, rationalization, and ego on financial statement fraud. The data used in this research is secondary data in the annual reports obtained through the Indonesia Stock Exchange (IDX) website. The population of this research is the banking listed on IDX in 2018 –2020. The sample selection in this research used a purposive sampling technique and resulted in 47 companies as the sample of research. This Research use quantitative methods. The analytical technique used are descriptive statistical and multiple linear regression. The results of this study indicated that collusion negatively affects financial statement fraud. Rationalization has a positive effect on financial statement fraud. Meanwhile, stimulus, capability, opportunity, and ego has no effect on financial statement fraud